Pengaruh Motivasi Kerja, Disiplin Kerja, Dan Kepemimpinan Terhadap Kualitas Pelayanan Publik Di Kantor Camat Teluk Nibung Kota Tanjungbalai - M.Abyadh Siahaan; Abdul Rahman (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to determine whether Work Motivation, Work Discipline and Leadership partially and simultaneously influence the Quality of Public Services at the Teluk Nibung District Office, Tanjungbalai City. This type of research is descriptive quantitative research. Based on the results of the t test, it shows that the Work Motivation variable has a significance value of 0.000 <0.05 with a calculated t value > t table (4.006 > 2.042), meaning that Work Motivation influences the Quality of Public Services. Work Discipline shows a significance value of 0.000 <0.05 with a calculated t value > t table (4.075 > 2.042), meaning that Work Discipline influences the Quality of Public Services. Leadership shows a significance value of 0.000 <0.05 and t count > t table (5.506 > 2.042), meaning that Leadership influences the Quality of Public Services. The F-test results show that the variables Work Motivation, Work Discipline, and Leadership collectively influence the Quality of Public Services, with a significance value of 0.000 < 0.05 and a calculated F value > F table (23.944 > 2.91).